Reproductive Growth and Development of Blueberry - Jeffrey G. Williamson; James W. Olmstead; Paul M. Lyrene (EDIS)
This revised 7-page fact sheet discusses flower bud initiation and development, pollination and fruit set, fruit development and yield, and the use of plant growth regulators. Written by J. G. Williamson, J. W. Olmstead, and P. M. Lyrene, and published by the UF Department of Horticultural Sciences, February 2012.